Successful Blunders: Reflection, Deflection, Teaching - Devan Cook (Journal of the Assembly for Expanded Perspectives on Learning, 2002)
Often we expect students' experience with assignments to reflect our own or those of previous students, but we may blunder when we base our teaching on past successes. By deflecting such assignments and constructing unexpected identities, students and instructors alike learn and teach.